2019
DOI: 10.1021/acs.inorgchem.9b00544
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry Breaking and Two-Step Spin-Crossover Behavior in Two Cyano-Bridged Mixed-Valence {FeIII2(μ-CN)4FeII2} Clusters

Abstract: Two new cyano-bridged mixed-valence {Fe III 2 (μ-CN) 4 Fe II 2 } clusters, {[(Tp)Fe III. Complexes 1 and 2•5MeOH exhibit gradual thermally induced two-step spin-crossover behavior (SCO) at two Fe II metal centers, and the transformation of high-spin (HS) to low-spin (LS) Fe II ions with temperature was confirmed by a combination of X-ray crystallography, variabletemperature Fourier transform infrared, variable-temperature magnetic susceptibility, and 57 Fe Mossbauer spectroscopy. Moreover, complexes 1• MeCN•Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…In addition, understanding the nature of multistep SCO may help in the development of more advanced functional materials. Multistep SCO can be caused by two different structural characteristics: the presence of nonequivalent metal centers, which undergo SCO at different temperatures, and symmetry breaking within the structure caused by a change in the space group or various host–host/host–guest interactions, which stabilize the intermediate states between purely HS and LS states. It is worth mentioning a number of cases in which the nature of the two-step SCO remains enigmatic because the complexes contain one crystallographically unique Fe­(II) center at all temperatures, and the values of all structural parameters (including bond lengths and angles) have an “average” HS/LS character at the plateau. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, understanding the nature of multistep SCO may help in the development of more advanced functional materials. Multistep SCO can be caused by two different structural characteristics: the presence of nonequivalent metal centers, which undergo SCO at different temperatures, and symmetry breaking within the structure caused by a change in the space group or various host–host/host–guest interactions, which stabilize the intermediate states between purely HS and LS states. It is worth mentioning a number of cases in which the nature of the two-step SCO remains enigmatic because the complexes contain one crystallographically unique Fe­(II) center at all temperatures, and the values of all structural parameters (including bond lengths and angles) have an “average” HS/LS character at the plateau. …”
Section: Introductionmentioning
confidence: 99%
“…To date, quite a few examples of materials showing multistep SCO behavior are known. , There are several examples of three-, four-, ,,, six/five-step spin transtions and even an example of a seven/eight-step spin transition. It should be noted that a significant number of such systems are Hofmann clathrate analogues, especially with dicyanometallic [M­(CN) 2 ] − (M = Ag, Au) fragments and pyridine derivatives (ranging from simple monosubstituted to more complicated ligand systems). , In these complexes, Fe­(II) ions have a pseudooctahedral coordination environment [FeN 6 ] with two axial azine ligands and four dicyanometallic [M­(CN) 2 ] − fragments that occupy equatorial positions.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the metal–organic interface in iron triazolate (Fe­(ta) 2 , Figure a) was shown to be dynamic, and a cooperative SCO effect was observed. Notably, the SCO transition is not a redox event, but rather a conversion between low- and high-spin Fe­(II). Since there are two dissimilar Fe­(II) centers housed within the Fe­(ta) 2 framework (Figure b, four Fe­(II) N1,3‑connected and two Fe­(II) N2‑connected per computational unit cell), SCO may inherently break symmetry, and we surmised that there may be “special” concentrations of HS­(Fe 2+ ) that may be preferentially stabilized throughout the SCO transition; i.e., one Fe environment may transition preferentially over the other. Alternatively, there may be a temperature-dependent “Devil’s staircase” throughout the SCO event; however, the steplike magnetization response to temperature has not been observed in Fe­(ta) 2 .…”
Section: Introductionmentioning
confidence: 96%
“…30–39 In various studies, scholars have prepared a series of low-dimensional polycyanide metal salt complexes whose structural backbone contains the Fe III –CN–M II sequence (M II = Fe II , Co II , and Mn II ), including bis, tri, tetra, octa, and pentadecanuclear complexes. 40–44 These molecules exhibit remarkable thermally induced SCO magnetic bistable properties. The primary synthetic strategies mentioned in the literature to bring out synergistic effects are: (1) covalent junctions (bridging ligands) to form coordination polymers, 45–48 (2) π–π stacking among the SCO sites, 49–51 and (3) hydrogen bonding.…”
Section: Introductionmentioning
confidence: 99%